الجرائم الإلكترونية المرتبطة بالإنترنت المظلم وتأثيرها على البيانات المحاسبية - مفيدة ضو الهواري; محمد الطاهر صقر; حنان الشيباني خليفة; سهيلة جمعة خليفة (Surman Journal of Science and Technology, 2025)
This study aims to shed light on cybercrimes associated with the dark web and their impact on accounting data. The dark web is a fertile ground for criminal activities, including data theft, financial fraud, and cyber extortion. The study explores the concept of the dark web, its characteristics, and the most prominent crimes conducted through it, focusing on how sensitive accounting data of companies and organizations are targeted. The research discusses the negative impacts of these crimes on the integrity of accounting data, the accuracy of financial reports, and the trust of investors and stakeholders. It also examines key preventive measures and modern technologies to combat such crimes, including strengthening cybersecurity, utilizing encryption, and employing artificial intelligence. The study highlights the importance of collaboration between governments and organizations to enhance legislation that combats cybercrimes on the dark web and ensures the protection of accounting data, thereby reducing risks and securing a safe digital environment for businesses.